2022
DOI: 10.1136/bmjdrc-2021-002558
|View full text |Cite
|
Sign up to set email alerts
|

Association of renin and aldosterone with glucose metabolism in a Western European population: the KORA F4/FF4 study

Abstract: IntroductionPrimary aldosteronism is associated with impaired glucose tolerance. Whether plasma aldosterone and/or renin concentrations are associated with type 2 diabetes and continuous measures of glucose metabolism in the general population is still under debate.Research design and methodsThe analyses included 2931 participants of the KORA F4 study at baseline and 2010 participants of the KORA FF4 study after a median follow-up of 6.5 years. The associations of active plasma renin and aldosterone concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…In patients with primary hyperaldosteronism, excessive aldosterone reduces insulin secretion in isolated islets and impairs insulin sensitivity in skeletal muscle and adipocytes [23], leading to a significantly higher risk of T2DM. However, this trend might not be readily transferable to a general population since T2DM cases in a general population are not associated with elevated aldosterone [24]. Normal pregnancy is associated with increased circulating renin, angiotensin II, and aldosterone [25], for an expansion of maternal plasma volume.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with primary hyperaldosteronism, excessive aldosterone reduces insulin secretion in isolated islets and impairs insulin sensitivity in skeletal muscle and adipocytes [23], leading to a significantly higher risk of T2DM. However, this trend might not be readily transferable to a general population since T2DM cases in a general population are not associated with elevated aldosterone [24]. Normal pregnancy is associated with increased circulating renin, angiotensin II, and aldosterone [25], for an expansion of maternal plasma volume.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive visceral fat distribution is linked to hypertension by several possible mechanisms involved in hormonal, inflammatory and endothelial alteration [ 50 ]. In an insulin resistant state, the presence of excessive visceral fat can stimulate reabsorption of sodium and urates at the tubular level [ 51 ]. Some studies also consider the possibility of leptin to predict the onset of hypertension [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that leptin acts on adrenocortical cells to increase CYP11β2 expression and directly activates aldosterone secretion which modulates hypertension in female mice [ 53 , 54 ]. In addition, leptin also elicits symphato-exitatory effects which ensues the activation of RAAS [ 51 ]. A study showed that leptin acts as an autocrine mediator of Ang II-induced cardiomyocyte hypertrophy in hypertensive LVH rats, in which the treatment of telmisartan improves the myocardial remodeling in rats by inhibiting RAAS activity and leptin levels [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, osteoporosis, adiposity and estrogen deficiency have been identified as risk factors for T2D [193][194][195]. The renin-angiotensin-aldosterone system is positively correlated with T2D and hypertension [196][197][198][199]. Anti-hypertensive medications that block the RAAS have been evidenced to have osteoprotective effects [3,[200][201][202][203][204][205].…”
Section: Discussionmentioning
confidence: 99%